THE CONTRIBUTION OF STUDENTS TEAM ACHIEVEMENT DIVISION (STAD) AND MOTIVATION TOWARDS WRITING (THE STUDENTS OF ENGINERING FACULTY MUHAMMADIYAH UNIVERISTY OF METRO) - Fenny Thresia (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2012)
The purpose of the present study is to explore the positive effects of Student Teams Achievement Division (STAD) on other important factors such as students’ motivation. STAD was used with thirty second-grade students and was compared to thirty second-grade students who worked in groups lacking the key components of STAD. Both groups completed pretest and posttest and responded in motivational questionnaire which measured changes in exposure to writing skill in English. The findings showed that (1) there was a significant progress within each group, (2) there was also significant mean difference between the experimental and control group with the contribution of the STAD approach to students’ motivation and to writing achievement.